Improving Students' Creativity through the Discovery Learning Model in Indonesian Language Learning - Nursalim Nursalim; Dian Purnomo; Nurkhadizah Hasibuan; Putri Rahma Dani (Jurnal Inovasi Pendidikan dan Sains, 2025)
The decline in students' creativity in Indonesian language learning is often caused by teaching methods that lack innovation. Many educators still use the conventional lecture method, which does not actively engage students in the learning process. This affects the low level of students' creativity, as seen from their lack of ability to think critically, communicate, and express new ideas. This study aims to analyze the effectiveness of the Discovery Learning method in improving students' creativity in Indonesian language learning. The method used in this study was a qualitative approach with a descriptive method, involving Indonesian language teachers and students as research subjects. Data were collected through interviews, observations, and documentation. The results of the study show that the Discovery Learning method can improve students' creativity in critical thinking, writing, and communication. Students become more active, independent, and have higher learning motivation. Thus, this method is recommended to be applied more widely in Indonesian language learning to improve students' creativity